The teachers’ satisfaction in higher education institutions as key factor of the strategic management and of the organizational competitiveness - Veloso, Cláudia M. (2020)
Currently Higher Education Institutions (HEIs) are operatizing in the massively competitive international environment. The present society asks important challenges to current HEIs in several issues: technological, managerial, academic and economic. Consequently, organizations define and adopt strategies that support high performance and organizational competitiveness, with particular attention to human resources as a key factor in the efficient implementing of it strategy. In this regards, professional satisfaction adopts a growing interest in understanding quality of professional life and its influence on strategic management and organizational competitiveness. High job satisfaction contributes to the professional finding meaning in his professional activity and to adoption positive attitudes towards organizational performance. In this perspective, the article purposes to verify if there are differences in socio-demographic, professional, training and labour variables related to the level of satisfaction of the teachers that belong to the HEIs of the Kwanza South Province (Angola). As well as to know the level of satisfaction of those professionals. The results show that the level of teachers’ satisfaction is positive and allows understanding the determinants of teachers’ satisfaction and their mastery in strategic management and competitiveness of the HEIs of Kwanza South Province.